Effects of Cryogenic Storage on Human Amnion Epithelial Cells - Srinivasan, Raghuraman C. (Cells, 2020)
Perinatal stem cells and epithelial cells isolated from full term amnion membrane, in particular, have attracted interest over the last decade, as a promising source of multipotent cells for cellular therapies. Human amnion epithelial cells (hAEC) have been used to treat monogenetic liver disease such as maple syrup urine disease or fibrosis of the liver in preclinical studies. In most studies xeno-transplants of hAEC were conducted without providing immunosuppression to recipients, reflecting the tolerogenic properties of hAEC. For many cell types, successful cryopreservation is critical for providing a readily available, off-the-shelf product. In this study, hAEC were isolated from full-term human placenta from 14 different donors, cryopreserved using a protocol and reagents commonly adopted for epithelial cell preservation. The cells were analyzed in terms of survival, recovery, and homogeneity, profiled for surface markers characteristic of epithelial, mesenchymal, endothelial, or hematopoietic cells. There were no significant differences observed in the percentage of cells with epithelial cell markers before and after cryopreservation. The relative proportion of stromal and hematopoietic cells was significantly reduced in hAEC preparations after cryopreservation. The expression of stem cell and immunomodulatory molecules were confirmed in the final product. Since multipotent cells are readily available from full-term placenta, this novel cell source might significantly increase the number of patients eligible to receive cellular therapies for liver and other diseases.